2021
DOI: 10.3390/ijms22126381
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Naturally Derived Compounds in Telomerase and Telomere Modulation in Skin Senescence and Aging

Abstract: Proper functioning of cells—their ability to divide, differentiate, and regenerate—is dictated by genomic stability. The main factors contributing to this stability are the telomeric ends that cap chromosomes. Telomere biology and telomerase activity have been of interest to scientists in various medical science fields for years, including the study of both cancer and of senescence and aging. All these processes are accompanied by telomere-length modulation. Maintaining the key levels of telomerase component (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 180 publications
0
7
0
Order By: Relevance
“…The telomerase consists of the catalytic telomerase reverse transcriptase subunit, known as TERT, and an RNA component (hTR) that works as a template for telomere extension [ 62 , 63 , 64 ]. The canonical functions of telomerase are related to telomere length maintenance and genome stability, while the non-canonical functions are involved in the regulation of non-telomeric DNA, alterations in cell cycle kinetics, the rise of proliferation, chromatin remodeling and more ( Table S1 ) [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The telomerase consists of the catalytic telomerase reverse transcriptase subunit, known as TERT, and an RNA component (hTR) that works as a template for telomere extension [ 62 , 63 , 64 ]. The canonical functions of telomerase are related to telomere length maintenance and genome stability, while the non-canonical functions are involved in the regulation of non-telomeric DNA, alterations in cell cycle kinetics, the rise of proliferation, chromatin remodeling and more ( Table S1 ) [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sugimoto et al [ 84 ] also reported the association between telomere length of the skin with chronical aging and photoaging confirming previous observations done by Kosmadaki and Gilchres [ 85 ]. Jacczak et al [ 86 ] claimed that maintaining the key levels of telomerase component (hTERT) expression and telomerase activity that provide optimal telomere length, as well as some non-telomeric functions, represents a promising step in advanced anti-aging strategies, especially in dermocosmetics.…”
Section: Oxidative Stress and Skinmentioning
confidence: 99%
“…An observational study on 3194 Americans older than 45 years showed that every increase of 20 µg/Se intake was associated with 0.42% longer telomere length in all participants [ 142 ]. In their paper, Jacczak et al [ 86 ] concluded that natural compounds, such as vitamin E, polyphenols, and Se, able to provide optimal telomere length could represent advanced anti-aging skin strategies. Another major actor of skin aging is the accumulation of advanced glycation end products [ 63 ].…”
Section: Seleniummentioning
confidence: 99%
“…The oxidative-stress-induced overexpression of hTERT in mitochondria has been shown to limit UV-induced mtDNA damage and mutagenic agents (e.g., ethidium bromide) and to protect mitochondrial DNA by reducing the cellular production of superoxides and ROS [ 21 , 35 , 36 ]. Other studies reported impaired mitochondrial function due to the reduced expression of hTERT, which manifested in increased or decreased membrane potentials, changes in the mtDNA copy number, and altered mitochondrial mass and ATP levels [ 37 , 38 , 39 ]. An association between the mitochondrial localization of hTERT and the drug resistance of cancer cells was also observed [ 38 , 40 , 41 ].…”
Section: Canonical and Noncanonical Functions Of Telomerasementioning
confidence: 99%
“… Association between hTERT, key signaling pathways, and senescence (acc. [ 21 , 22 , 39 ], modified). The hTERT subunit of telomerase can be involved in various metabolic pathways (e.g., NFκB, Wnt/β-catenin, and adhesion as well as senescence) and affect the expression of various genes.…”
Section: Figurementioning
confidence: 99%